Splenic marginal zone lymphoma: A case report and review of the literature - Prachi,; Aiyer, Hema Malini (Indian Journal of Case Reports, 2020)
Splenic marginal zone lymphoma (SMZL) is a low-grade B-cell non-Hodgkin’s lymphoma characterized by massive splenomegaly, moderate lymphocytosis with or without villous lymphocytes, rare involvement of peripheral lymph nodes, and indolent clinical course. SMZL has a distinct immunologic profile which when correlated with the morphologic findings of peripheral blood and bone marrow aspirates as well as clinical and hematologic features enables accurate diagnosis and obviates the need for further invasive diagnostic procedures. Here, we present a case of SMZL who presented with massive splenomegaly and was diagnosed on the basis of clinical, hematological, and characteristic immunophenotypic findings on bone marrow aspirate and biopsy.